Kemampuan Menyimak Bahasa Jerman Melalui Media Fun Easy Learn Deutsch - Febriani Vikria; Hasmawati Hasmawati; Misnah Mannahali (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This study aims to determine the planning, implementation, and results of improving German listening skills through the Fun Easy Learn Deutsch media for students of class XI MIPA 3 MAN 1 Makassar. This research is a classroomaction research which consists of two cycles, each of which contains planning, implementation, observation and reflection. The research data consists of two types, namely qualitative data which is a description of the results of the implementation and results of observations during the learning process and quantitative data in the form of average test results for students' listening skills presented in percentage form. The average score of students' listening skills in class XI MIPA 3 in cycle I was 65.63 (Good) and increased in cycle II to 82.30 (Very Good). The results of this study indicate that the Fun Easy Learn Deutsch application can improve students' listening skills in German during learning.Keywords: Learning Media, Listening Skills, Germany, Fun Easy Learn Deutsch Application